Liquid chromatography high resolution mass spectrometry for the determination of baclofen and its metabolites in plasma: Application to therapeutic drug monitoring. (17th February 2017) - Labat, Laurence; Goncalves, Antonio; Marques, Ana Rita; Duretz, Bénédicte; Granger, Bernard; Declèves, Xavier
Abstract: Baclofen is used to manage alcohol dependence. This study describes a simple method using liquid chromatography coupled to high‐resolution mass spectrometry (LC‐HR‐MS) developed in plasma samples. This method was optimized to allow quantification of baclofen and determination of metabolic ratio of its metabolites, an oxidative deaminated metabolite of baclofen (M1) and its glucuronide form (M2). The LC‐HR‐MS method on Exactive® apparatus is a newly developed method with all the advantages of high resolution in full‐scan mode for the quantification of baclofen and detection of its metabolites in plasma. The present assay provides a protein precipitation method starting with 100 μL plasma giving a wide polynomial dynamic range ( R 2 > 0.999) between 10 and 2000 ng/mL and a lower limit of quantitation of 3 ng/mL for baclofen. Intra‐ and inter‐day precisions were <8.1% and accuracies were between 91.2 and 103.3% for baclofen. No matrix effect was observed. The assay was successfully applied to 36 patients following baclofen administration. Plasma concentrations of baclofen were determined between 12.2 and 1399.9 ng/mL and metabolic ratios were estimated between 0.4 and 81.8% for M1 metabolite and on the order of 0.3% for M2 in two samples.